The trajectory of general movements from birth until 12-14 weeks corrected age in preterm infants born before 33 weeks' gestation and weighing less than 1500g : a descriptive study - Van Zyl, Reze (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScPhysio)--Stellenbosch University, 2019.